MEDIA BALOK UNTUK MENINGKATKAN KEMAMPUAN MENGENAL GEOMETRI PADA ANAK USIA DINI DI RAUDHATUL ATHFAL NURUL RABI’AH KECAMATAN KAWALU KOTA TASIKMALAYA - Asep Mumung; Tetin Nurfitri; Ai Rosmiati (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2021)
This study aims to describe learning planning and learning implementation in the ability to recognize geometry with block media in early childhood in Raudhatul Athfal Nurul Rabi'ah Kawalu District, Tasikmalaya City. The research method used is a descriptive qualitative approach. The sample of this study was 1 teacher and 15 children of group B. The results of the analysis of the research data obtained that in making learning plans refer to Permendikbud (Regulation Indonesian Ministry of Education and Culture) number 137 and number 146 of 2014. The steps taken by the teacher in playing blocks to improve the ability to recognize geometry that is with a playing environment footing, footing before playing, footing when playing and footing after playing. The activity is one of the learning plans in stimulating 6 (six) development aspects contained in the design of the Weekly Learning Implementation Plan (RPPM) and the Daily Learning Implementation Plan / RPPH. The block media that is used when learning the introduction of geometric shapes is a standard block which is safe to use for young children and meets the requirements to be used as learning media. The ability of children to recognize geometric shapes with block media can be said to be developing as expected.